2016
DOI: 10.1039/c6ra23886f
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and self-healing films based on the dynamic Schiff base linkage

Abstract: In this study, we report highly transparent self-healing films based on Schiff base linkages between DF-PEG and CS via a layer-by-layer technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…However, it was hard to demonstrate that the Schiff base linkage formed in the film from FT-IR characterization. 20,23,24 This was probably due to the peak of CO at 1665 cm −1 (amide I) transferred to 1629 cm −1 , which overlapped with the characteristic peak of Schiff base linkage (CN) as literature reported. 25−27 The film was further characterized by XPS.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…However, it was hard to demonstrate that the Schiff base linkage formed in the film from FT-IR characterization. 20,23,24 This was probably due to the peak of CO at 1665 cm −1 (amide I) transferred to 1629 cm −1 , which overlapped with the characteristic peak of Schiff base linkage (CN) as literature reported. 25−27 The film was further characterized by XPS.…”
Section: Resultssupporting
confidence: 60%
“…In the FT-IR spectrum of the films, the peak at 1569 cm –1 disappeared which preliminarily demonstrated that the amino groups of AMCS3 have been reacted with aldehyde groups of ADA50. However, it was hard to demonstrate that the Schiff base linkage formed in the film from FT-IR characterization. ,, This was probably due to the peak of CO at 1665 cm –1 (amide I) transferred to 1629 cm –1 , which overlapped with the characteristic peak of Schiff base linkage (CN) as literature reported. …”
Section: Resultsmentioning
confidence: 87%
“…Compared with the spectrum of TPA, the absorption band of aldehyde group disappeared for ShSP-3, and a new –N CH– bond at 1650 cm −1 appeared, indicating the successful polymerization of ShSP-3. 38,39 Simultaneously, the amine group can attack epoxy structure to break the epoxy groups (at 912 cm −1 ) in the DGEBA, and the hydroxyls are created after ring-opening reaction. 40 …”
Section: Resultsmentioning
confidence: 99%
“…The modified chitosan films should have characteristic CQN imine stretching vibration peaks at 1635 cm À1 , stronger than APAU and plain chitosan peaks in this range, confirming the presence of imine in the modified biopolymer. 64,65 The intensity of the imine peak as well is expected to increase with the increase in APAU content. However, the presence of amide CQO has made distinguishing the peak difficult as it lies within the same region.…”
Section: Spectroscopic Analysismentioning
confidence: 99%